MUAMMOLI VAZIYATLAR USULINING BIOKIMYO FANINI O’QITISHDA O’ZIGA XOS XUSUSIYATLARI - Amonova, H.I.; Niyazov, L.N.; Nikolayev, Ye.L. (SCIENCE and SOCIETY, 2021)
The article provides theoretical information and practical recommendations on the use of the problem based learning method in teaching biochemistry in Higher Medical Education. It was found that the use of problem based learning in the process of learning develops students’ practical skills and creativity.